2020
DOI: 10.1089/whr.2019.0014
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Methods Study Exploring Older Womens' Attitudes Toward Osteoporosis Medications: Adapting a Health Communication Framework

Abstract: Background: Bisphosphonates (BPs) can reduce fracture risk for adults with osteoporosis (OP), but they have rare risks, complicating decision making. Guided by an established health decision and communication framework, we explored older women's feelings and positions toward taking BPs. Materials and Methods: Using a mixed-methods design, we interviewed women >65 years of age who had never taken BPs. After learning about BPs, participants responded to items about their feelings toward medication benefits/risks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In five studies ( n =1010) [ 220 , 221 , 224 , 229 , 230 ], adults (primarily females) ≥50 years old were provided information on the benefits and harms of treatment in various formats; not all participants in these studies were considered to be at high fracture risk or eligible for treatment. In these studies, patients were asked to make hypothetical treatment decisions, with results of three studies showing that patients’ preference for treatment versus no treatment may be highly variable (3 studies, n =317; low certainty) [ 220 , 221 , 224 ]. Two other studies showed that after receiving information on their personal fracture risk (median [IQR] 10-year hip fracture risk 2.2 [0.5–2.7%] in one study, 5-year hip fracture risk 1.4 [0.8–3.0%] in the other), relatively few (19 to 39%) patients may be willing to accept treatment (2 studies, n =593; low certainty) [ 229 , 230 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In five studies ( n =1010) [ 220 , 221 , 224 , 229 , 230 ], adults (primarily females) ≥50 years old were provided information on the benefits and harms of treatment in various formats; not all participants in these studies were considered to be at high fracture risk or eligible for treatment. In these studies, patients were asked to make hypothetical treatment decisions, with results of three studies showing that patients’ preference for treatment versus no treatment may be highly variable (3 studies, n =317; low certainty) [ 220 , 221 , 224 ]. Two other studies showed that after receiving information on their personal fracture risk (median [IQR] 10-year hip fracture risk 2.2 [0.5–2.7%] in one study, 5-year hip fracture risk 1.4 [0.8–3.0%] in the other), relatively few (19 to 39%) patients may be willing to accept treatment (2 studies, n =593; low certainty) [ 229 , 230 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of 8794 unique records retrieved by the searches for KQ4, we assessed 146 for eligibility by full text and included 12 studies (5 cross-sectional [220][221][222][223][224], 4 cohort [225][226][227][228], 3 RCTs [229][230][231]) and one associated publication of another study [53] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations